Minimum Wage Policy Effects on Economic Growth - Siti Nur Aishah, Mohd Hashim (2012)
The purpose of this study is to examine the relationship between minimum wage policy and economic growth for the period 2000 – 2005. To achieve the objective, we estimate a growth model by employing the panel ordinary least square (OLS) and panel estimated generalized least square (EGLS) method. A sample consists of 61 countries with and without minimum wage and 33 were used in this study. For the minimum wage measure, we used minimum wage dummy, excess wage and minimum wage ratio to GDP as separate variables. We also include additional variables namely initial GDP, population growth, investment, trade openness, government expenditure and gross enrolment ratio. The results of the study show that, first, countries with minimum wage policy have higher economic growth. Second, the level of minimum wage does not affect economic growth for the countries that have the minimum wage policy. Based on the findings, countries should implement minimum wage policy since it would increase income for the worker and at the same time have positive effect on economic growth. The results also support the minimum wage policy that will be implemented in Malaysia.